Functions of Taboo Words Found in ‘Habits’ Song Lyric by Eminem - Kadek, Dian Trisna Yanti; Santika, I Dewa Ayu Devi Maharani (LITERA : Jurnal Bahasa Dan Sastra, 2025)
The use of taboo language could be found easily in our daily life, especially in our daily communication because it is considered more effective to use to express feelings and any situations. This research deals with the taboo words found in ‘Habits’ song lyric by Eminem. Theory of taboo words Wardhaugh (2006) is used to analyse the data found. This research aims to analyse the functions of taboo words in ‘Habits’ song lyrics by Eminem. The data of this research were taken from a rap song entitled ‘Habits’ by an American famous rapper, Eminem. As a result of this study, there are 4 functions of taboo words found in ‘Habits’ song lyric. The most functions used in the song lyrics is to draw attention and to show contempt with the percentages 35,7%.